Toronto ACHD program: A 65 year legacy - J.M. Colman; W.G. Williams; C.K. Silversides; L. Harris; L. Benson; J. Heggie; R. Alonso-Gonzalez; E. Oechslin (International Journal of Cardiology Congenital Heart Disease)
The Toronto Adult Congenital Heart Disease (ACHD) Program at the University Health Network, University of Toronto, began in 1959. It traces its origins to a Paul Wood protégé, Dr. John Evans, and to a long-standing and supportive relationship with Hospital for Sick Children (SickKids), located just across the street. Over the decades, the program has grown to become a major center for training and research in ACHD and one of the largest clinical programs for ACHD care globally. This paper recounts the 65-year history of the program, including some of its key individuals, challenges, milestones, innovations, discoveries, and future aspirations.